Functional and biochemical inflammatory responses to low-dose intra-articular recombinant equine IL-1β: a pilot study - Korac, Lindsay; St. George, Lindsay; MacNicol, Jennifer; McCrae, Persephone; Jung, L.; Golestani, N.; Karrow, Niel; Cánovas, Angela; Pearson, Wendy (Frontiers in Veterinary Science, 2026)
Low-dose intra-articular injection of recombinant equine interleukin-1β (reIL-1β) may offer a useful model for studying early onset or subclinical joint inflammation in horses. This pilot study aimed to determine the lowest intra-articular dose of reIL-1β required to produce biochemical evidence of synovitis, and to correlate synovitis biomarkers with functional, upper-body asymmetry parameters. Saline (control) and 50, and 75 ng reIL-1β were injected into the left or right intercarpal joint of three (n = 3) horses in a three-way crossover design. Synovial fluid was collected by aseptic arthrocentesis immediately prior to reIL-1β injection (0 h), and at 6-, 12- and 24-h after injection. Synovial fluid was analyzed for inflammatory [prostaglandin E2 (PGE2) and nitric oxide (NO) and cartilage turnover (glycosaminoglycan (GAG)] biomarkers. Prior to each arthrocentesis, subjective (AAEP score) and objective [inertial measurement unit (IMU)] gait analysis was performed. Asymmetry parameters (MinDiff and MaxDiff) were calculated using IMU data from the poll and pelvis. Mixed model analysis and Spearman correlation coefficient compared biomarker and gait biomechanics data between doses. PGE2 concentrations increased significantly (p < 0.05) at 6- and 12-h following 50 ng reIL-1β, and at all time points following 75 ng injection, without significantly affecting NO and GAG concentrations (p > 0.05). Injection of 75 ng reIL-1β significantly increased poll MinDiff at 6- and 12-h, which was positively correlated with PGE2 concentration (ρ = 0.35, p < 0.05). Findings support the utility of this lower-dose reIL-1β model for inducing a mild, transient inflammatory response, without overt functional changes, which upholds principles of ethical animal research.